Anaerobic Production of a Biosurfactant by Bacillus licheniformis JF-2 - Javaheri, Mohammad (1985)
Bacillus licheniformis JF-2 anaerobically produced a biosurfactant when grown in a glucose-mineral salts medium containing yeast extract and NaNO(3). Surface tension of the medium was reduced from 70 to 74 mN/m to as low as 28 mN/m due to the production of an anionic biosurfactant.